2012
DOI: 10.3892/mmr.2015.3397
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg3 sensitizes human non-small cell lung cancer cells to γ-radiation by targeting the nuclear factor-κB pathway

Abstract: At present, it is elusive how non-small cell lung cancer (NSCLC) develops resistance to γ-radiation; however, the transcription factor nuclear factor-κB (NF-κB) and NF-κB-regulated gene products have been proposed as mediators. Ginsenoside Rg3 is a steroidal saponin, which was isolated from Panax ginseng. Ginsenoside Rg3 possesses high pharmacological activity and has previously been shown to suppress NF-κB activation in various types of tumor cell. Therefore, the present study aimed to determine whether Rg3 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…Activated NF‐κB eventually binds to κB elements in the promoter region of target genes and initiates the transcriptional process of numerous genes . Recent investigations have demonstrated that the NF‐κB pathway is suppressed by a large number of ginsenosides, including Rg1, Rh2, Rb1, Compound K (CK), Rg3, Rb3, Rd, Pseudoginsenoside‐F11 (PF11), Re, Rh1, Rf, 20( S )‐protopanaxatriol, and Ro (Fig. ).…”
Section: Cellular Stress Response Mechanisms Regulated By Ginsenosidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Activated NF‐κB eventually binds to κB elements in the promoter region of target genes and initiates the transcriptional process of numerous genes . Recent investigations have demonstrated that the NF‐κB pathway is suppressed by a large number of ginsenosides, including Rg1, Rh2, Rb1, Compound K (CK), Rg3, Rb3, Rd, Pseudoginsenoside‐F11 (PF11), Re, Rh1, Rf, 20( S )‐protopanaxatriol, and Ro (Fig. ).…”
Section: Cellular Stress Response Mechanisms Regulated By Ginsenosidesmentioning
confidence: 99%
“…Moreover, Rh1 blocked the invasion and migration of human astroglioma cells ; (2) the enhancement of cancer cell sensitivity by ginsenosides has also been documented. Rg3 sensitized nonsmall cell lung cancer (NSCLC) to γ ‐radiation and 20( S )‐Rh2 improved the cellular pharmacokinetic behaviors and cytotoxicity of Adriamycin in Adriamycin‐resistant MCF‐7 cells; and (3) ginsenosides also directly inhibited the growth of human cancer. For example, Rg3 induced apoptosis and suppressed the growth of human melanoma cancer …”
Section: Cellular Stress Response Mechanisms Regulated By Ginsenosidesmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be a key mechanism behind the preventive effects of these 4 injections on RILI [36]. Ginsenoside Rg3 a main ingredient of ginseng extractions was able to sensitize A549 and H1299 lung carcinoma cells to γ -radiation and significantly enhance the efficacy of radiation therapy in C57BL/6 mice bearing a Lewis lung carcinoma cell xenograft tumor [52]. Radix Astragali in SQFZI and YZXJC is considered as potential and powerful exogenous source of antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…New approaches are needed to tackle this disease. As such, natural phytochemicals like ginsenosides or their derivatives have being studied for their potential in NSCLC treatment [25], [26], [27], [28], [29], [30].…”
Section: Introductionmentioning
confidence: 99%